Effervescent Tablet Formulation Melinjo Seed Extract (Gnetum gnemon L.) Using PEG 6000 As Lubricant and Citric Acid - Tartaric Acids As Acid Sources - Puput Andi Apsari; Dewi Nur Eka Sari; Aris Perdana Kusuma; Oktavia Indrati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Melinjo seeds (Gnetum gnemon L.) have antioxidant properties one of which is from phenol compounds. However, there is no pharmaceutical dosage form of melinjo seeds especially effervescent tablet. The purpose of this research was to determine the best variation of citric-tartaric acid and PEG 6000 from effervescent tablet of melinjo seed extract. The effervescent tablet of melinjo seed extract were formulated with variation of citric-tartaric acid 25%:75%, 65%:35%, 50%:50%, 20%:80% and PEG 6000 0%, 2%, 3%, up to 5%. The effervescent tablet were made by melting parts of acids and bases, added with extract and other ingredients. The evaluation included flow and powder tapping, tablet hardness, weight variation, friability, and tablet solubility test. The data were analyzed by comparing approaches based on the requirements of Pharmacopeia Indonesia V andUnited States of Pharmacopeia 36.Variations of equal amount of citric-tartaric acid produced hard effervescent tablets with small friability. The unbalanced acid concentration resulted in higher friability. The greater the concentration of citric acid resulted in the longer solubility of the tablet. The addition of PEG 6000 made the flow time of granules quicker, while higher concentrations would increase the hardness of tablets and accelerate the soluble time. Excessively high concentrations resulted in a high degree of friability. Variation of citric-tartaric acid and PEG 6000 influenced physical properties of granule and effervescent tablet extract of melinjo seeds, such as flowability, hardness, friability, and solubility of the tablet.